Mind Matters: Lessons From Past Crises for Child and Adolescent Mental Health During COVID-19 - UNICEF Innocenti Research Centre (United Nations, 2021)
COVID-19 is a crisis like no other in modern times. It has reached every population and community. While the evidence base is still nascent, this report looks at the impacts of disasters and past epidemics – such as Ebola, HIV, SARS/MERS and Zika – on child and adolescent mental health and psychosocial wellbeing, and examines how these insights can guide policies and progammes to support children, their families and communities during the current pandemic. COVID-19 – its associated public health responses and social and economic impacts – is likely to have multiple deleterious effects on mental health, including elevated risks of anxiety and depression, trauma, loss of family and friends, violence, loneliness and social isolation. However, this pandemic also offers opportunities for positive coping and resilience. While there is no magic formula to address the mental health and psychosocial impacts of crises, there are proven and promising interventions from past experiences to mitigate the impact today – especially for the most vulnerable children and adolescents. These include social protection, caregiver skills and support, community and social support, life skills and school based programmes, and specialized care, to name a few.